Tuning of Traction Power Station Converter Output Characteristics - Žižlavský, Petr; Mlynařík, Ladislav (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The paper defines the criteria that must be considered when setting the output control characteristics of the static frequency converter (SFC) stations for supplying the 25kV/50Hz railway catenary. The control characteristics must consider many often conflicting requirements and their optimal selection is therefore not a straightforward matter. The second part of the paper shows the search for the optimal control characteristic in terms of losses in the catenary.
Ladění výstupních charakteristik měniče měničové napájecí stanice
Keywords: Converters for Special Applications, Railway Power Stations, Simulation of Traction Grid; Měniče pro speciální aplikace, železniční napájecí stanice, simulace trakční sítě